Potential Roles of microRNAs in the Regulation of Monoamine Oxidase A in the Brain - Higuchi, Yuki; Soga, Tomoko; Parhar, Ishwar S. (Frontiers in Molecular Neuroscience, 2018)
Monoamine oxidase A (MAO-A) is an enzyme that regulates the levels of monoamine neurotransmitters, such as serotonin, noradrenaline and dopamine, and it has been used as a therapeutic target for depression. However, MAO-A inhibitors, which directly acts on MAO-A protein, have limited use due to their adverse effects. MicroRNAs (miRNAs) are 18-22 nucleotide long, small non-coding RNAs, which have recently emerged as regulators of protein levels that could potentially be new therapeutic targets for psychiatric disorders. This review article aims to discuss the current status of the treatment for depression with MAO-A inhibitors and the regulatory factors of MAO-A. Further, the review also proposes possible regulatory mechanisms of MAO-A by miRNAs, which leads to better understanding of the pathology of depressive disorders and their potential use as therapeutic agents.